Effects of secretin gene knockout on the diversity, composition, and function of gut microbiota in adult male mice - Zhang, Fengwei; Tao, Zhengyi; Chen, Congjia; Chow, Billy Kwok Chong (Frontiers in Cellular and Infection Microbiology, 2023)
The gut microbiota plays a vital role in maintaining gastrointestinal homeostasis, however, whether it is influenced by gut hormones remains unknown. Secretin is a well-known gastrointestinal hormone produced by enteroendocrine S cells. This study utilized 16S rRNA amplicon sequencing to characterize the effect of SCT deficiency on the gut microbiota. Our results show that systemic SCT knockout alters the composition and abundance of the mouse gut microbiota but does not affect fecal short-chain fatty acids and lipids concentrations. At the genus level, the abundance of Turicibacter, Bacteroides, Ruminococcu, Romboutsia, Asaccharobacter, and Parasutterella increased in SCT-/- mice, whereas the abundance of Akkermansia and Escherichia decreased. Functional prediction results showed that lack of SCT reduced the abundance of carbohydrate metabolism-related pathways but increased the abundance of linoleic acid metabolism and branched-chain amino acid degradation. Overall, systemic SCT knockout had only minor effects on gut microbiota composition and function in adult male mice fed a standard chow diet.